Measuring the impact of environmental regulation on pig farmers’ production decisions: evidence from Jiangsu Province, China - Zhang, Feng; Yang, Yongbing; Ge, Yang; Hu, Hao (Frontiers in Environmental Science, 2026)
As the world’s largest pig producer, China’s stable pig production is closely linked to global food security. Amid increasingly stringent environmental governance, environmental regulation has become a critical factor shaping pig farmers’ production decisions. However, it remains unclear how different types of environmental regulation instruments affect farmers’ production scale decisions during China’s ongoing transition from small-scale to large-scale pig farming, and through what mechanisms these effects occur. Based on panel survey data from 323 pig farms across 22 counties in Jiangsu Province, China, this study empirically examines the impact of environmental regulation on farmers’ production scale decisions and explores the underlying mechanisms using a fixed effects model. The results show that different types of environmental regulation instruments exert distinct effects on production scale decisions. Increasing the intensity of control-based environmental regulation leads to a contraction in production scale, whereas strengthening incentive-based regulation promotes production scale expansion. Moreover, the effects of environmental regulation are heterogeneous across farms of different sizes. Specifically, intensified control-based environmental regulation has a more pronounced negative impact on large-scale farms, while incentive-based regulation significantly encourages expansion only among small- and medium-scale farms. These findings contribute to a better understanding of how environmental regulation shapes production decisions in the livestock sector and offer policy-relevant insights for optimizing regulatory design to balance environmental protection and production stability. The study also provides empirical evidence for other developing countries facing similar structural transformations in livestock farming.